Fra Confucio e il Prozac. Tendenze attuali della psichiatria cinese - Aliquò, Maria Chiara (Il sogno della farfalla, 2005)
Nowadays Chinese psychiatry has a fundamentally organicistic approach to mental disease in line with Western models, especially those coming from America. The article offer a review of the development of psychiatric and psychological sciences in China and points to those factors that have contributed to the spreading of such an organicistic approach. The article also examines the knowledge of Freudian theories in china and elaborates on the reason why it has never developed as a clinical method of therapy, finding some followers only among writers and literary critics. Chinese psychology and psychiatry have been influenced by many factors, such as peculiar political an economical developments, traditional culture and human resources. China’s present national policy of reforms and openness to the outside world, has had a great impact on the advancement of interest in the psychological field. However, in order to interpret mental phenomena and behavior of the Chinese people, attention must also be focused on the theoretical constructions of China’s ancient psychological heritage traced through traditional Chinese culture.